Examining the Use of Information Systems to Preserve Indigenous Knowledge in Uganda: A Case from Muni University - Oroma, Josephat O.; Guma, Ali (I.J. Modern Education and Computer Science, 2018)
Indigenous Knowledge (IK), can be preserved using Information Systems in order to protect cultural heritage and disseminate local knowledge for development. This knowledge often passed on orally for generations has become significant in searching for answers to several world's critical problems, are at risk of becoming extinct. This "traditional wisdom" is highly useful in solving complex problems of health, agriculture, education, use of natural resources and the environment. The main challenges of IK are inadequate documentation and diminishing transmission channels. Both descriptive and quantitative methods are used in this study that focuses on highlighting the importance of indigenous knowledge in the sustainable development process and illustrating ways in which technology can be used to preserve it, thereby enriching the development process from a holistic perspective. This research strengthens the preservation of local IK, enhances its adoption in the formal educational settings, leads to improvement in scientific knowledge development and inspire sustainable community development using a holistic approach.
Keywords: Information Systems; Indigenous Knowledge; ICT